Problems of Theory and Practice of Synthetic Stylistics in Uzbek Compound Sentences (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the theory of synthetic stylistics in Uzbek compound sentences, its application in practice, examples, stylistic errors and similar issues.